Graphic analysis of the obtained results on cotton regeneration - Khuramova, Khadicha (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, samples of cotton fibers (selected industrial grades such as S-65-24 I/1, Bukhara-102 I/1, and Andizhan-36 I/1), obtained in the ginning process after the newly created regeneration of cotton linters in cotton waste coming from the cotton ginning unit of the UHK, were tested in the laboratory system HVI (High Volume Instruments). According to the results of all tests, it was established that the cotton fibers are suitable for spinning.